Applied behavior analysis (ABA) on the emotional development of autistic children - Badi'ah, Atik; Mendri, Ni Ketut; Nugroho, Heru Santoso Wahito (Jurnal Kesehatan Ibu dan Anak, 2020)
The development of autistic children both physically, emotionally, intellectually, and psychosocially has a problem that results in the inhibition of children reaching a level of emotional development that is appropriate to their age. Applied Behavior Analysis (ABA) in children with autism includes autistic children providing emotional, social, informational, and practical support. An autistic child will feel that he is loved and wanted if more and more people in the family environment love and care for him. The purpose of the study was to know the effect of Applied Behavior Analysis (ABA) on the emotional development of children with autism. This type of quantitative research uses a Quasi-experiment with the design Pre-test Post-test with Control Group Design. The observation was carried out twice. The first observation is to determine the emotional development of an autistic child before being given Applied Behavior Analysis (ABA) and the second observation after being given Applied Behavior Analysis (ABA). Sampling was done by purposive sampling with the criteria of parents and autistic children aged 6-12 years in the autistic schools of the provinces of Yogyakarta and Ponorogo, East Java. Analyzed analytically using paired t-test and Wilcoxon, with a significant level of p <0.05. the emotional development of children with autism in the experimental group before Applied Behavior Analysis (ABA) was given to most categories were good of only 34 children with autism (73.9%) and after Applied Behavior Analysis (ABA) most categories were good for 44 autistic children (95.7%). In the control group before most were less as many as 28 children with autism (60.9%) and after most good as many as 17 children with autism (37.0%).The experimental group pre-test and post-test with a value of p (sig) 0.000, meaning there is a difference between pre-test and post-test in the experimental group. In the control group pre-test and post-test with p-value (sig) 0.000 meaning there is a difference between pre-test and post-test in the control group. There was an effect of Applied Behavior Analysis (ABA) on the emotional development of autistic children.